The impact of cannabis on endurance and performance of athletes - risks and benefits - a literature review - Nojek, Paweł; Błaszczyński, Gustaw; Nowotarska, Agnieszka; Pawlik, Wiktoria; Zimonczyk, Mariusz; Zawół, Monika (Journal of Education, Health and Sport, 2024)
Introduction and Objective. Cannabis, particularly its active compounds THC (tetrahydrocannabinol) and CBD (cannabidiol), has gained attention in the sports community for its potential therapeutic benefits. Researchers are exploring its use in managing pain, reducing inflammation, enhancing recovery, and alleviating anxiety, making it appealing for treating both acute injuries and chronic conditions in athletes. While CBD is considered safe, THC can impair cognitive functions, potentially affecting performance and increasing the risk of injury. Unlike THC, CBD is not prohibited by the World Anti-Doping Agency (WADA) and is well-tolerated in humans. Methods. A literature review was conducted using PubMed and Google Scholar, searching terms like "CBD", "THC", "cannabinoids", "physical activity", and "medical marihuana". Articles from the last five years were prioritized. Brief description of the State of Knowledge. Cannabinoids interact with the body’s endocannabinoid system (ECS) and are classified into phytocannabinoids (from cannabis), endocannabinoids (produced by the body), and synthetic cannabinoids (man-made). The two most studied phytocannabinoids are THC, which is psychoactive, and CBD, known for therapeutic benefits like anxiety reduction without intoxication. THC activates both CB1 receptors (in the brain) and CB2 receptors (in immune cells), while CBD modulates these receptors indirectly. Cannabinoids show potential in managing chronic pain, inflammation, and neurological conditions, with some studies suggesting they could replace opioids for pain relief. They may help in injury recovery among athletes. Conclusions. The consumption of CBD and THC offer both benefits and risks. However, there is insufficient evidence on the direct impact of cannabis use on athletes beyond its role in pain management and recovery. Further research is needed to provide stronger evidence on their effects in sports.